Biological control and growth promotion in Solanum spp. - Klint, Johannes; Zeiner, Niklas (SLU/Dept. Of Plant Biology, 2020)
Potato (Solanum tuberosum) is Sweden’s most treated crop in terms of chemical disease control, primarily to prevent potato late blight caused by Phytophthora infestans. Another important disease is potato early blight caused by Alternaria solani. In this thesis biological disease control was explored as a supplement or an alternative to chemical disease control. The idea was to isolate, identify and apply bacteria on potato plants and examine their effects on growth and disease control.